1998
DOI: 10.1080/000155598441864
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Irritation in Older and Younger Skin: a Comparison

Abstract: Changes in stratum corneum properties due to sodium lauryl sulfate cumulative irritation were determined as a function of age. We irritated the backs of 7 younger (27.7 +/- 4.6 years, mean +/- standard deviation) and 10 older (69.8 +/- 5.5 years) volunteers on 5 consecutive days with open application of a 7.5% aqueous sodium lauryl sulfate solution. Water- and untreated skin served as controls. Transepidermal water loss, stratum corneum capacitance, Desquamation Index, and skin roughness parameters were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…[10][11][12] However, other endogenous factors including age and sex showed no association with skin symptoms. Although other studies indicated that the younger age group is more susceptible to irritants, 13,14 our study showed a similarly high prevalence of skin symptoms in all age groups except the ages of 20 to 29 years. This could be explained by the fact that the majority of this age group were army personnel (82.0%).…”
Section: Discussioncontrasting
confidence: 66%
“…[10][11][12] However, other endogenous factors including age and sex showed no association with skin symptoms. Although other studies indicated that the younger age group is more susceptible to irritants, 13,14 our study showed a similarly high prevalence of skin symptoms in all age groups except the ages of 20 to 29 years. This could be explained by the fact that the majority of this age group were army personnel (82.0%).…”
Section: Discussioncontrasting
confidence: 66%
“…2c). It was found that CNT/aPDMS has much lower modulus (27.5 kPa) than PDMS (~1 MPa); this value is comparable to that of skin (130 kPa)2526. This low modulus enhances the mechanical matching of the large electrode to soft skin and increases its ability to penetrate skin wrinkles.…”
Section: Resultsmentioning
confidence: 97%
“…Although fast and convenient direct methods that are appropriate for the clinical setting have been developed based on interference fringe profilometry and the use of CCD cameras [26,27,28], the preparation of replicas remains the most frequently used technique with a vast body of data available [3,4,5,8,10,12,13,17,18,29,30,31]. The advantages of the replica technique are simple and rapid sample preparation, reproducibility and precision, and the possibility to store the replica for repeated measurements [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Roughness was reported to vary significantly between different sites, being largest in the posterior neck and smallest in the upper back and lower leg, while only minor differences between genders and races were shown [8,9]. Surface topography was further used to assess the results of intervention on skin, for example, by moisturizing agents [10], antiaging products [6], laser surgery [11], chemical irritants [12], and vitamin analogs [13]. …”
Section: Introductionmentioning
confidence: 99%